Analyzing the Interaction and Consequences of International Financial Merger & Acquisitions on Nonresident Alien Rates for Higher Education Leadership in the United States - Frederick, Duane T.; Kasztelnik, Karina (Journal of Accounting and Finance, 2022)
The study used this data to determine the effect between time and merger status upon the DVs of revenue, fall enrollment rates, and nonresident alien rates beginning the AY of the Financial M&A event and 5 years after the event. The results of the study do indicate that nonresident alien rates did grow favorably over the five years for both Financial M&A HEIs and non-merging HEIs but that the interaction effect between time and merger status upon nonresident alien rates was not significant. This suggests that other factors caused growth in nonresident alien rates apart from M&A activity. Researchers have noted that globalization has become an increasing factor in higher education and that there exists increasing competition for nonresident alien students. Therefore, the most effective means of improving nonresident alien rates seems to lie somewhere other than Financial M&A initiatives.